(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2015)
Venture capital investments are an important source of funds particularly useful for start-ups and companies at a very young stage of their life. It is therefore necessary to promote venture capital activity as well as entrepreneurship to boost innovation and economic growth. The public sector role is important in stimulating these activities. We analyze the main policy levers consistent with achieving this objective successfully, and check if the Spanish public program Fond-ICO Global follows them.